Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper reviews the factors that may explain high and persistent unemployment in Canada, with particular emphasis on the role that a decline in the relative cost of capital may have had on trend unemployment. The analysis suggests that in Canada a declining trend in the cost of capital, associated with technological changes and innovations, has been an important factor in explaining the rise and persistence of unemployment. The paper also analyzes recent trends in personal saving in Canada and macroeconomic effects of the government debt.